Bionanomaterials for industrial applications - Ahmed, Shakeel 1989- (CRC Press, Taylor & Francis Group, 2025)
Bionanomaterials for Industrial Applications is a comprehensive guide to the current state of bionanomaterials research and their prospective applications in a variety of industrial sectors. The book discusses the properties of bionanomaterials, types and their potential applications in various disciplines, such as biomedicine, food industry, environment, etc. It provides a comprehensive overview of the current state of bionanomaterials research and their potential applications, making it an indispensable resource for anyone interested in learning more about this dynamic and rapidly developing field.
Keywords: Aufsatzsammlung